Morfologi Urban Artefak Kampung Kota - Anityas Dian Susanti; Ikaputra Ikaputra (Prodi Arsitektur Universitas Matana, 2020)
This paper discusses the morphology of urban kampong which includes the morphology of urban urban kampong artifacts, by first defining what urban kampong morphology is. The discussion in this paper is still general and can still be developed more about the morphology of urban artifacts in urban kampong. Kampung kota is part of an urban area that has Indonesian characteristics. This paper uses the method of studying literature using several references related to morphology. And the references used are those related to morphology and urban kampong. The result of this paper is that the morphology of urban kampong artifacts is that settlements in a city generally occur unplanned. Unplanned parts of urban areas are referred to as settlements that make up cities with morphological principles consisting of streets, plots and buildings.